Wave energy potential and variability for the south west coasts of the Black Sea: The WEB-based wave energy atlas - Bingolbali, Bilal; Jafali, Halid; Akpinar, Adem; Bekiroglu, Serkan (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
This study aims at the assessment of wave energy potential and its spatial and temporal variability along the south-west coasts in the hot-spot areas of Black Sea. For this purpose, third-generation numerical wave hindcast model Simulating WAve Nearshore (SWAN), which is based on a set of nested SWAN model with increasing spatial resolutions (a coarse grid, then a fine grid, and then three sub-grids), forced with the Climate Forecast System Reanalysis (CFSR) winds is used to produce long term wave characteristics during the 31 years in the areas of interest. For the south-west coasts of the Black Sea the best nested SWAN model configuration, developed in our previous studies [1,2], with tuned coefficients for all of the deep and shallow water source terms in modelling of the wind-generated waves is run to obtain spatial and temporal outputs of several wind wave parameters for the assessment of wave energy potential and its variability. By using this data set, temporal and spatial variability of wave energy potential along the south western Black Sea is analysed in detail, considering annual, seasonal, and monthly spatial variation maps of wave power for each of the sub-grids. In addition, annual, seasonal, and monthly wave power potential variability, the exceedance probability curves, the value of wave energy resource potential, and wave power roses are established for several locations. The value of energy density, spatial variation of the stability of energy density (the coefficient of variation, monthly variability index, seasonal variability index, and persistency analysis), spatial variation of total storage and exploitable storage of wave energy resource are also analysed. Finally, it was determined that in the regions (Karaburun SD3 sub-grid domain) where the average wave energy flux is high, the wave energy flux has a high coefficient of variation, and thus the regions (Filyos SD2 sub-grid domain) having lower wave energy flux have a stable wave energy flux which is ideal for energy exploitation from waves. Annual average wave energy in the southwestern part of the Black Sea is concentrated at 0.2-1.5 m significant wave height range, and also the concentration is between 2 and 5 s in Karaburun SD3, 3-7 s in Filyos SD2 and 2.5-6.5 s in Sinop SD1 sub-grid domains in terms of the wave energy period. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Wave energy; Potential; Variability; Hotspots; Southwestern black sea; RESOURCE ASSESSMENT; HIGH-RESOLUTION; WIND; GULF; ASSESSMENTS; OMAN; Science & Technology - Other Topics; Energy & Fuels